The Relationship Between Animated Caricature Media Use and Vocabulary Mastery and Anecdotal Text Ability - Ihsan, Mohd Bahaudin; Ismawati, Esti; Tukiyo, Tukiyo (Indonesian Journal of Advanced Research, 2025)
This study aims to analyze the relationship between the use of animated caricature media and vocabulary mastery on the ability of students in class X of MA Al-Kautsar Pekanbaru in writing anecdotal texts. Using a correlation quantitative method with 30 students as a random sample, data was collected through questionnaires and anecdotal writing tests. The results of the analysis showed that all instruments were valid and reliable, as well as normal and homogeneous distributed data. The t-test and the F-test showed a significance value of 0.000, while the regression coefficient test showed an effect of 95%. These findings show that animation caricature media and vocabulary mastery together contribute strongly to students' ability to write anecdotal texts.